2020
DOI: 10.1016/j.idcr.2020.e00931
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related Cryptococcus neoformans choroiditis

Abstract: We describe a case of Cryptococcal choroiditis in a person with advanced HIV/AIDS. A 29-year-old male with AIDS presented with fever, photophobia, and ataxia secondary to cryptococcal and toxoplasma meningoencephalitis. Dilated fundoscopic examination revealed bilateral and multifocal posterior infiltrates consistent with cryptococcal choroiditis. Treatment with parenteral and intravitreal liposomal amphotericin B, oral flucytosine, and oral trimethoprim-sulfamethoxazole led to resolution of his symptoms and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Conversely, involvement of the choroidal regions is exceptionally uncommon, representing a mere 3% of occurrences as ascertained through postmortem investigations [ 6 ]. Furthermore, it has been reported that chorioretinal involvement is linked to hematogenous dissemination of cryptococcus through the choroidal vasculature, rather than contiguous infection through the meninges, unlike most ocular presentations [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, involvement of the choroidal regions is exceptionally uncommon, representing a mere 3% of occurrences as ascertained through postmortem investigations [ 6 ]. Furthermore, it has been reported that chorioretinal involvement is linked to hematogenous dissemination of cryptococcus through the choroidal vasculature, rather than contiguous infection through the meninges, unlike most ocular presentations [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic treatment can be complemented by intravitreal injections of amphotericin B, but there are no clear guidelines, and therefore, it is conducted on an individualized basis. Vigilant monitoring of antiretroviral therapy is crucial to prevent an immune recovery reaction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases were reported in patients with concomitant immunosuppression. Previous cases were reported in patients with advanced AIDS [ 8 10 ] or with T cell leukemia [ 11 ]. As described in the latter cases [ 8 , 9 ], EDI-OCT and ICG have proven most useful in directing the diagnostic algorithm in panuveitis in immunosuppressed patients by defining the localization of lesions and assessing response to treatment.…”
Section: Discussionmentioning
confidence: 99%